Sociolinguistic influences on nicknaming political leaders and connotations in media platforms: Reference from former presidents of Tanzania - Borra, Edward Edward (Teaching English as a Foreign Language Journal, 2025)
Nicknames are a fascinating issue to explore, acting as alternative of names or familiar forms of proper names, often reflecting personality traits, physical characteristics or relationship. In social interactions, nicknames add more meanings, represent sociality, identity, intimacy or social reputation. Though, a lot have been written on nicknames, little has been said to public figures. This study analyses the connotations of former presidents of Tanzania nicknames and their social political and implications. The qualitative study which informed by Symbolic Interactionism Theory. The data were carried on five (5) media, from which three were mass media, namely newspapers, radio and television. While on the hand of social media, YouTube and TikTok were involved to depict the presidents’ nicknames. In giving translation of the Presidents’ nicknames, semi-structured interview was combined to collect opinions about interpretations of those presidents’ nicknames. The findings in this study were presented thematically. It was revealed that Tanzanian presidents’ nicknames were given basing on the two main ways; formal and informal. It was seen that behaviours, characters, habit, physical appearances and residential areas were reasons behind for nicknames. Also, the findings indicated that each society interprets nicknames based on their social ideology and beliefs.